Co-Expression of Plexin-B1 and Met in Human Breast and Ovary Tumours Enhances the Risk of Progression - Guido Valente; Giuseppina Nicotra; Marisa Arrondini; Roberta Castino; Lorena Capparuccia; Maria Prat; Simonetta Kerim; Luca Tamagnone; Ciro Isidoro (Cellular Oncology)
Background: Plex-B1, the receptor of Sema4D, has been implicated in tumour growth, angiogenesis and metastasis. The binding of Sema4D to Plex-B1 can trigger the activation of Met tyrosine kinase, thereby promoting cell dissociation and invasive growth. We tested the hypothesis that the expression of Plex-B1, either alone or in association with Met, can be of predictive value for tumour progression.